KEDUDUKAN MANAJEMEN SUMBER DAYA MANUSIA PENDIDIKAN ISLAM DI ERA GLOBALISASI - Aldo Redho Syam; Syamsul Arifin (AL-ASASIYYA: Journal Of Basic Education, 2017)
It is undeniable that the competition between Islamic educational institutions in globalization era is getting stronger and sharper, not only companies that compete, in the world of education can not be separated from the name of competition, so from here then the name of human resources Islamic education should be really encouraged to race toward the quality of human resources of Islamic education better and have a strong competitiveness, especially in the current globalization era. Human resources of Islamic education should be demanded continuously to be able to develop themselves actively and have the initiative to continue to think more advanced. The human resources of Islamic education here, must really be the human resources of Islamic education who have a high commitment to learning, have a strong willingness to guard the change towards the better, they must have a high work ethic and full of spirit without stopping to learn, so that their potential can be developed and can be felt by himself, especially Islamic educational institutions that desperately need their fighting spirit, in developing and advancing the institution in globalization era.